Pengaruh Debt To Assets Ratio, Current Ratio, Quick Ratio, Terhadap Nilai Perusahaan Yang Terdapat Pada Sektor Perdagangan Jasa Dan Investasi Yang Terdaftar Pada Bei Periode 2015-2019 - ananda Alexander Aritonang; kelvin kelvin; Mariska Sisilia (CERED Indonesia Institute, 2021)
This study aims to find out and analyze the effect of the debt to assetsu ratio, currentu ratio,u and quicku ratio to the value of your company that exists in your trading sector and services and investments that are listed on the BEIu for the 2015-2019 period.u The research approach used is a quantitative approach.u The sampling method is purposive sampling, and the sample is 18u companies in the trade, services, and investments that are registered on the Indonesian stock exchange for 5u years and the period of research is significant. The tou equity ratio has an effect and is partially significant to the priceu tou book value in the trade, services and investment sectors that are listed on the I Indonesia Stock Exchange, with the results of the test, you get the value of u 2.947u with a significant value nu is 0.004u while u ttabelu is u 1.987u with u significant 0.05.u Current ratiou has no effect and partially significant to u priceu tou booku valueu in your trading sector, services and investment that you listed on the I Indonesia Stock Exchange,